Condições para a caracterização de infrações contra a ordem econômica envolvendo direitos de propriedade intelectual no Brasil - Alves, Joyce Ruiz Rodrigues (2018)
This master dissertation has as its purpose, by means of a review of doctrine and case law, to attempt to reply to two questions, namely: How to ascertain the lawfulness or unlawfulness of the exercise of intellectual property rights from an antitrust policy perspective? What are the conditions should be met to allow a conclusion regarding the lawfulness of the exercise of intellectual property rights in relation to antitrust policy? Our conclusion is that the conditions for the configuration an antitrust infringement are different for two groups: (a) antitrust infringements arising from the exercise of unlawful intellectual property rights; and (b) antitrust infringements arising from the abuse of intellectual property rights. Antitrust infringements arising from the exercise of unlawful intellectual property rights refer to situations in which the holder has committed frauds in the administrative proceeding in order to obtain the intellectual property right and the exercise of those rights has led to an actual or potential injury on competition. In its turn, antitrust infringements arising from the abuse of intellectual property rights encompass two main situations. The first refers to a situation in which an economic agent attempts to leverage its market power in the market in which it holds its intellectual property rights to another market concerning another product in which it is not entitled to any protection and this conduct results on an injury on competition. The second refers to a situation in which an economic agent attempts to use intellectual property rights to prevent or delay the launch of a new product by a rival and this leads to an injury on competition